2023
DOI: 10.1007/s10461-022-03949-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Preferences for Long-Acting Injectable Antiretroviral Therapy Among Adolescents and Young People Living with HIV in South Africa

Abstract: Long-acting injectable anti-retroviral therapy (LAART) may overcome barriers to long-term adherence and improve the survival of adolescents and young people living with HIV (AYLHIV). Research on the acceptability of LAART for this age-group is limited. We asked 953 AYLHIV about their preferred (theoretical) ART mode of delivery (pill, injectable, or other) in 2017–2018, before LAART was available or known to AYLHIV in South Africa. One in eight (12%) AYLHIV preferred LAART over single or multiple pill regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Of all study-eligible adolescents, 1046 were recruited and participated at the baseline of the study in 2014-2015, 979 (94.0%) of these were followed up at the second wave (2016-2017) of the study, 953 (91.1%) at the third wave (2017-2018), and 35 (3.4%) died during the study period. A more detailed description of the study design and data collection procedures is available elsewhere, 32,33 and further study information, including study protocol, is available at www.mzantsiwakho.org.za.…”
Section: Methodsmentioning
confidence: 99%
“…Of all study-eligible adolescents, 1046 were recruited and participated at the baseline of the study in 2014-2015, 979 (94.0%) of these were followed up at the second wave (2016-2017) of the study, 953 (91.1%) at the third wave (2017-2018), and 35 (3.4%) died during the study period. A more detailed description of the study design and data collection procedures is available elsewhere, 32,33 and further study information, including study protocol, is available at www.mzantsiwakho.org.za.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that a significant proportion of patients may be initiating antiretroviral therapy at a later stage of HIV disease, which can lead to increased risk of opportunistic infections and mortality (UNAIDS, 2021). Early initiation of antiretroviral therapy is crucial for achieving and maintaining good health outcomes for people living with HIV (Hung et al, 2022;Toska et al, 2023). HIV treatment guidelines recommend initiating antiretroviral therapy as soon as possible after diagnosis, regardless of CD4 count, in order to achieve viral suppression and reduce the risk of HIV transmission (Sarıgül Yıldırım et al, 2023).…”
Section: Causes Of Treatment Failurementioning
confidence: 99%
“…Several researchers have used different statistical models to predict its epidemiology, such as HIV/AIDS-related cases and their development, which have resulted in the current achievement of undetectable and non-transmissible outcomes among people living with the virus [ 2 , 3 , 4 ]. Some researchers used logistic regression to predict the influence of the early risk factors of SARS-CoV-2 ART associated with the advancement of the disease, and the findings showed that vaccination and early treatment with antivirals have significantly reduced the risk of disease progression.…”
Section: Introductionmentioning
confidence: 99%